A perovskite oxide LaCoO3 cocatalyst for efficient photocatalytic reduction of CO2 with visible light. Issue 18 (13th February 2018) - Qin, Jiani; Lin, Lihua; Wang, Xinchen
Abstract : As a unique class of functional materials, perovskite oxides have shown great opportunities in various energy storage and conversion applications. Abstract : As a unique class of functional materials, perovskite oxides have shown great opportunities in various energy storage and conversion applications. However, their performance for boosting photocatalytic CO2 reduction is seldom reported. Herein, we report a facile synthesis of coralline-like LaCoO3 perovskite materials and their use as highly efficient and stable cocatalysts for splitting CO2 into CO with visible light.